HUBUNGAN PENILAIAN “BENAR-SALAH” DALAM PENERJEMAHAN (Sebuah Kajian Awal) - Ayup Purnawan (Adabiyyāt: Jurnal Bahasa dan Sastra, 2008)
The evaluation or judgment of a translation is not a matter of right or wrong because the process of translation involves several aspects, which takes a serious attention. Those aspects are intra-lingual, target as well as source language, and extra-lingual aspect. Those aspects connect each other in a translation process. This papers aims to elaborate the complexities of those aspects by giving examples and to explain their effects in a translation process.